The Effect of Corporate Social Responsibility and Leverage on Tax Planning With Institutional Ownership As A Moderating Variable - Mita Rusliani; Bani Binekas (UNIVED Press, 2026)
This study aims to assess the effect of Corporate Social Responsibility (CSR) and leverage on tax planning, with institutional ownership as a moderating variable. The population consists of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sample was selected using purposive sampling and employed a quantitative approach using Moderated Regression Analysis (MRA). The results show that CSR does not have a significant effect on tax planning, meaning that the amount of CSR expenditure does not directly affect a company's ETR. Meanwhile, leverage has a positive and significant effect on tax planning, indicating that the use of debt is related to changes in tax burdens through interest expenses. Institutional ownership was unable to moderate the relationship between CSR and tax planning, but it was proven to weaken the effect of leverage on tax planning. Simultaneously, the model's ability to explain tax planning was still relatively low, with a coefficient of determination value below 10 percent, indicating that tax planning practices in the food and beverage sub-sector were more influenced by factors other than the research variables. These findings confirm that companies in this sub-sector are more focused on operational stability, regulatory compliance, and public legitimacy than on aggressive tax saving strategies